The construction of the training process highly skilled athletes in soccer and field hockey in the annual cycle of training - Kostyukevych, V. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The purpose of the study - to justify the theoretical and methodological principles and concepts of the training process of building highly skilled athletes in soccer and field hockey in the annual cycle of training. The results . Calculate the ratio of training loads of different orientation in the annual cycle of training. Means of producing football players in the annual training cycle is as follows: non-specific (general training exercise) - 45.6%, specific - 54.4% (special training exercise - 4.1% subsidiary - 22, 7%, competitive - 27.6% ). Means of producing players in the annual training cycle is as follows: non-specific (general training) exercise - 49.0%, specific - 51.0% (special training - 2.3% subsidiary - 26.1%, competitive exercise - 22.0% ). Key words